Distribution patterns of the creative class in Hamburg: “openness to diversity” as a driving force for socio-spatial differentiation? - Pohl, Thomas (ERDKUNDE, 2008)
In urban and regional research, planning practice, and urban policy, the spatial distribution of creativity and openness to diversity is increasingly receiving attention. However, to date, there have been few empirical findings concerning the local distribution of these dimensions of socio-spatial differentiation hardly. Using the example of Hamburg, Germany, we try to measure the socio-spatial distribution of these dimensions by secondary data analysis and analyze the patterns of segregation. The socio-spatial development in Hamburg’s neighbourhoods in the recent years is analyzed in order to address the issue of whether urban quarters that are very open to diversity in lifestyles show tendencies of revaluation. Our findings show that the socio-cultural symbols of the creative class do play an important role for the socio-spatial structure of the city today, but that a high rate of openness to diversity does not entail improvements in socio-spatial development.